Should Angiotensin Receptor Neprilysin Inhibitors Replace Angiotensin-converting Enzyme Inhibitors in Heart Failure With a Reduced Ejection Fraction? - Hayman, Sam (Card Fail Rev, 2016)
Angiotensin-converting enzyme inhibitors (ACEIs) have been the cornerstone of treatment of heart failure with reduced ejection fraction (HFrEF) for over two decades. Inhibition of neprilyisin augments vasoactive substances including natriuretic peptides, which may have multiple advantageous effects in chronic HF. Early studies of neprilyisin inhibition led to drug discontinuation due to lack of efficacy or safety concerns. Sacubitril/valsartan is a first-in-class combined angiotensin receptor/neprilysin inhibitor (ARNI). The PARADIGM-HF study demonstrated robust superiority of ARNI compared with enalapril in patients with chronic symptomatic HFrEF, raising the question of whether ACEI should still have a role in the management of HFrEF.